Numerical and experimental analyses of ablation measurements in expansion wind tunnel facilities using a new plasma pre-heating technique - Daniel Odion Iyinomen (International Journal of Thermofluids, 2020)
A new technique for preheating axisymmetric samples of heat shield material has been demonstrated through this work. Future applications for the technique are expected to be found in expansion tube facilities that can simulate the true flow energy under re-entry conditions. This new technique was applied to graphite sample ablation. A 50 mm diameter graphite disc having a thickness of 2 mm, was heated from the downstream side with a plasma to approximately 2500 K, and then exposed to a cold Mach 4.5 flow. The disc was mounted on an experimental probe which was very similar to the European standard probe, normal to the flow. The experiments show a significant spatial variation in thickness loss for the graphite test material over the disc radius though the spatial variation was still largely axisymmetric. The CFD results only included the reaction chemistry during flow over the heated disc and did not consider the mechanical actions, such as erosion and spallations. The analysis shows that numerical simulation of the oxidation rate produced results that were within 50% of the mass loss measurements. Simulations indicate that oxidation through surface reactions producing CO was the major contributor to the ablation losses. Analysis involving comparisons between the experiments and simulations suggests that mechanical actions of the ablation process are only minor contributors to mass loss. The experimental material loss included losses while the heating cycle occurred for the heated-only, and heated-with-flow runs. This pre-heating part of the heating cycle was taken into account for the comparison with simulation. Experimentally measured mass loss for the heating cycles were averaged and assumed to apply for the mass loss during the heating phase of the heated-with-flow runs. The potential for mechanical actions to explain the difference between simulation and experimental results is investigated. Presented here are the analyses of results, investigating material loss characteristics, and considers the discrepancy between experimental and CFD determination of the ablation rates.